Evaluation of two techniques for irrigation/aspiration retrolental viscoelastic removal in cataract surgery - Fernando Aguirre Balsalobre; Paz Orts Vila; Fernando Hernández Pardines; Víctor García Conca; Sara Núñez Márquez; José Ramón Hueso Abancéns (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2020)
Purpose: To compare surgical results after phacoemulsification using two different techniques for removal of Ophthalmic Viscoelastic Device (OVD).  Methods: A randomized prospective study was conducted on 77 patients who underwent cataract surgery. In the first group, OVD was removed over the optic by small abrupt horizontal and vertical displacements of the IOL. In the second group OVD was removed by placing the I/A probe behind the IOL. Intraocular Pressure (IOP), Intraocular Lens Position (IOLP) and refraction were analyzed over the first six weeks. Results: Results in both groups were similar in axial length, keratometry, intraocular lens, age, sex, spherical equivalent and anterior chamber depth. IOP, refraction and IOLP were similar after surgery, and no statistically significant differences were found. The mean refractive change along the first six weeks was 0.33 diopters for the first group (removal only over the IOL) and 0.28 diopters in the second group (P= 0.38). IOL shifting along the firsts six weeks was of 0.18 mm for the first group and 0.11 mm for the second group. The difference between groups for this parameter, nearly reached statistical significancy (P= 0.057). No complications were reported with this maneuver. Conclusions: The aspiration of retrolental OVD (behind the IOL) appears to be a safe maneuver, but it has not proved to offer any advantages. According to our results, displacing the retrolental OVD by subtle taps on the IOL has been enough to avoid secondary postoperative intraocular pressure spikes and IOL shifting in first 6 weeks.